Extensão da interação para a integração humano-computador à luz da teoria da engenharia semiótica - Glívia Angélica Rodrigues Barbosa (2024)
The rise of autonomous technologies (e.g., semi-autonomous vehicles and intelligent virtual assistants) is changing the relationship between humans and technologies so that the interaction era is evolving into the human-computer integration era. Unlike the stimulus-response relationship that occurs in the traditional HCI interaction, in the integration era, users and technologies are physically and/or conceptually integrated, and they become partners establishing a symbiotic relationship to achieve common goals. For this reason, HCI researchers have defined and characterized a new interaction paradigm, the Human-Computer Integration (HInt), which extends the focus of the HCI field to encompass this new partnership relationship between humans and technologies. The HInt paradigm presents new challenges and opportunities for the HCI Community. Among these challenges, we can highlight the demands for extending the scope of HCI theories and methods to explore the impacts, design, use, and evaluation of HInt. As HInt is an emerging paradigm, these demands can be explored from different theoretical perspectives, including from the Semiotic Engineering Theory perspective. Thus, this thesis aims to extend the Semiotic Engineering scope so that this theory can also encompass the HInt as a paradigm that extends the traditional HCI. To achieve this goal, we have conducted a qualitative research methodology that involved the characterization of HInt within the HCI scope, as well as the extension of Semiotic Engineering concepts, ontology, and methodology to cover the HCI with a lens on HInt. As results, this thesis presents: (1) an overview of the current state of knowledge and research agenda for HInt from the HCI perspective; (2) the extension of the Semiotic Engineering theoretical framework to define and characterize HInt; and (3) the Semiotic Inspection Method for HInt (MIS-HInt) to support the design and evaluation of partner technologies. These results are useful and contribute to (a) advancing knowledge and (b) evolving HInt in light of Semiotic Engineering.